(untitled) (Asian Business Research, 2022)
Under the background of "dual circulation", to implement the international investment concept of "bringing in" and "going global", it is urgent to realize the coupling and coordinated development of IFDI and OFDI. On the basis of trying to explore the coupling and coordination mechanism of two-way FDI in Jinan City, this paper uses the system coupling evaluation model to measure the coupling degree and coupling coordination degree. The results show that from 2003 to 2020, the coupling degree of two-way FDI in Jinan was at a high level of coupling, but the coupling coordination degree was low.